Artificial Intelligence (AI) Role in Financial Literacy in the Banking Channels: Mobile Apps and Physical Branches - Rahman, Abdul (Journal of Economics and Management, 2024)
The integration of Artificial Intelligence (AI) in the banking sector is transforming financial literacy initiatives by offering personalized, accessible, and interactive learning experiences. This study examines the impact of AI interventions on financial literacy improvement through a two[1]way ANOVA analysis, considering two independent variables: demographics (age groups) and banking channels (mobile apps vs. physical branches). Findings indicate significant improvements in financial literacy among younger users (18–35) and higher effectiveness of AI-driven tools in mobile apps compared to physical branches. Additionally, the interaction effect reveals that demographic-specific strategies are essential for maximizing AI's impact. This research underscores AI’s potential to bridge knowledge gaps and promote financial inclusion by tailoring educational tools to diverse customer needs.